2018
DOI: 10.1007/s00784-018-2344-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of technical errors and periapical lesions in a sample of endodontically treated teeth: a CBCT analysis

Abstract: Evaluation of endodontic treatment quality that considers every single root canal aims on warning dental practitioners of the prevalence of technical errors that could be avoided with careful treatment planning and execution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 41 publications
6
50
0
4
Order By: Relevance
“…A recent study found that the most frequent error in root filled premolars was underfilling (Nascimento et al . ). This result is similar to the present findings, except for RCC type IV, V and ‘other’, for which the most common error was nonfilled canals.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent study found that the most frequent error in root filled premolars was underfilling (Nascimento et al . ). This result is similar to the present findings, except for RCC type IV, V and ‘other’, for which the most common error was nonfilled canals.…”
Section: Discussionmentioning
confidence: 97%
“…In situations where more than one technical error was diagnosed, the most common association found in the present study was underfilling and nonhomogeneous filling, as reported by Nascimento et al . (). Both conditions are strongly associated with a greater risk of developing periapical diseases as it may facilitate bacterial growth (Liang et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…) and endodontic technical errors (Nascimento et al . ), more recent data using an ex vivo approach (Kruse et al . ) have suggested that diagnosis of AP in filled roots using CBCT is less accurate.…”
Section: Discussionmentioning
confidence: 99%